Fabrication and characterization of printed zinc batteries - M. A. Nazri; Anis Nurashikin Nordin; L. M. Lim; M. Y. Tura Ali; I. Mansor; Muhammad Irsyad Suhaimi; R. Othman; S. R. Meskon; Z. Samsudin (Bulletin of Electrical Engineering and Informatics, 2021)
Zinc batteries are a more sustainable alternative to lithium-ion batteries due to its components being highly recyclable. With the improvements in the screen printing technology, high quality devices can be printed with at high throughput and precision at a lower cost compared to those manufactured using lithographic techniques. In this paper we describe the fabrication and characterization of printed zinc batteries. Different binder materials such as polyvinyl pyrrolidone (PVP) and polyvinyl butyral (PVB), were used to fabricate the electrodes. The electrodes were first evaluated using three-electrode cyclic voltammetry, x-ray diffraction (XRD), and scanning electron microscopy before being fully assembled and tested using charge-discharge test and two-electrode cyclic voltammetry. The results show that the printed ZnO electrode with PVB as binder performed better than PVP-based ZnO. The XRD data prove that the electro-active materials were successfully transferred to the sample. However, based on the evaluation, the results show that the cathode electrode was dominated by the silver instead of Ni(OH)2, which leads the sample to behave like a silver-zinc battery instead of a nickel-zinc battery. Nevertheless, the printed zinc battery electrodes were successfully evaluated, and more current collector materials for cathode should be explored for printed nickel-zinc batteries.